Preferable Interior Elements On Instagram Photos At Contemporary Coffee Shops - Setiamurti Rahardjo (Mudra Jurnal Seni Budaya, 2018)
Today we are facing an era where the massive usage of Instagram has been utilized as a means of competitive marketing between hospitality industries, namely coffee shops. The more hashtags of a particular coffee shop indicate its prospect to gain popularity and win the market competition. Instagram users also benefits the coffee shop owners through their personal photo documentations that become a costless marketing. Although there have been numerous discussions about how aesthetic interior design and visual advertising increases the customer visits to coffee shops, there is still a lack of information about specific interior elements that are frequently framed on Instagram photos. Thus, this paper aims to explore interior elements on Instagram photos at contemporary coffee shops in order to find a particular interior element or setting which is more preferable as a photo background or object. This study is performed through the content analysis method with Instagram photo samples of 180 Coffee and Music, Mimiti Coffee and Space, Sejiwa, and Sydwic, all of which have more than a thousand hashtags on Instagram and represent various interior design styles. The result shows vegetation and concrete wall as the most preferred interior elements, accompanied by monochromatic color tone of the furniture or decoration. This result is able to contribute a form of knowledge to both designers and coffee shop owners to keep the continuation of this business industry by giving more considerations on the preferable interior elements.Sekarang ini Instagram sudah banyak digunakan dalam persaingan media marketing di antara berbagai industri bisnis, salah satunya kedai kopi atau populer disebut dengan coffee shop. Semakin banyak tanda tagar yang dimiliki sebuah coffee shop di Instagram sejalan dengan tingkat kepopuleran coffee shop tersebut dan kemungkinannya untuk memenangkan dunia persaingan. Para pengguna Instagram juga mendukung penngusaha dengan unggahan dokumentasi pribadi berupa yang dimanfaatkan sebagai marketing gratis. Meski pembahasan mengenai keterkaitan antara estetika desain interior dan marketing visual dan tingkat ketertarikan pengunjung, namun belum ada ulasan spesifik mengenai elemen interior apakah yang kerap muncul dalam foto-foto Instagram. Dengan demikian, artikel ini bermaksud untuk mengulas elemen interior pada coffee shop di era kontemporer, yang lebih disukai sebagai latar maupun objek foto. Penelitian untuk artikel ini dilakukan dengan metode konten analisis, dengan mengkaji sampel-sample foto dari 180 Coffee and Music, Mimiti Coffee and Space, Sejiwa, and Sydwic. Tempat-tempat tersebut memiliki lebih dari seribu tagar di Instagram dan mewakili penggayaan desain yang berbeda-beda. Penelitian ini memperlihatkan bahwa preferensi elemen interior untuk foto Instagram terletak pada keberadaan vegetasi dan tembok beton, yang disertai dengan penggunaan warna monokrom dari furnitur dan dekorasi yang ada di dalam ruang. Hasil ini kemudian dapat dipergunakan sebagai wawasan bagi desainer maupun pemilik usaha coffee shop untuk mempertimbangkan pengembangan usahanya melalui pengolahan elemen-elemen interior.